Magnetopause Surface Reconstruction From Tangent Vector Observations. Issue 12 (12th December 2018) - Collier, Michael R.; Connor, Hyunju K.
Abstract: Entire fields of science, most notably in astrophysics, rely on line‐of‐sight observations. In planetary science and heliophysics, the techniques of soft X‐ray and energetic neutral atom imaging also produce line‐of‐sight measurements. An important question is whether the geometry of the surface, for example, the magnetopause, can be reconstructed using only line‐of‐sight observations from a single spacecraft. Under a broad range of conditions, the peak emission corresponds to the tangent to the boundary surface, such as the planetary surface or magnetopause, the so‐called limb brightening phenomenon. Thus, line‐of‐sight observations frequently provide information concerning the tangent to the surfaces being observed. We present an algorithm to reconstruct the cross section of the magnetopause using line‐of‐sight soft X‐ray observations (and, in principle, energetic neutral atom observations). The algorithm successfully reconstructs the cross section of the magnetopause in the orbit plane. The three‐dimensional magnetopause structure can be recovered from observations by a spacecraft whose orbit precesses around the magnetosphere. Key Points: Peak X‐ray and ENA emission occurs along tangent line of sight Series of tangent observations allows surface reconstruction Algorithm reconstructs magnetopause from tangent observations